2018
DOI: 10.1002/jpen.1427
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Nondigestible Polysaccharides Ameliorate Colitis by Improving Gut Microbiota and CD4+ Differentiation, as Well as Facilitating M2 Macrophage Polarization

Abstract: Background The aim of this study was to investigate the therapeutic mechanism of a specific multifiber mix diet (MF) designed to match the fiber content of a healthy diet in interleukin‐10 knockout (IL‐10−/−) mice with spontaneous chronic colitis displaying similar characteristics to those of human Crohn's disease (CD). Methods Sixteen‐week‐old IL‐10−/− mice were used for the experiments with MF diet for 4 weeks. Severity of colitis, the composition of the fecal microbiota, expression of Th1/Th17 cells, myelop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Several studies have demonstrated that dysregulated intestinal immune response and mucosal inflammation induced by dysbiosis also contribute to mucosal epithelial barrier dysfunction and progression of IBD. , In particular, the regulation of macrophage polarization through the transplantation of gut microbiota is a promising effective target for colitis. , In addition, intestinal inflammation during the development of colitis is characterized by enhanced pro-inflammatory cytokines levels . Furthermore, the toll-like receptor 4 (TLR4)/nuclear factor-kappa B (NF-κB) and NOD-like receptor pyrin domain-containing protein 3 (NLRP3) inflammasome signaling pathways mediate the pathogenesis of intestinal inflammation. , Thus, the macrophage polarization modulation and inflammatory cytokine production by modulating various inflammatory signaling pathways can be a potential therapeutic approach for colitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that dysregulated intestinal immune response and mucosal inflammation induced by dysbiosis also contribute to mucosal epithelial barrier dysfunction and progression of IBD. , In particular, the regulation of macrophage polarization through the transplantation of gut microbiota is a promising effective target for colitis. , In addition, intestinal inflammation during the development of colitis is characterized by enhanced pro-inflammatory cytokines levels . Furthermore, the toll-like receptor 4 (TLR4)/nuclear factor-kappa B (NF-κB) and NOD-like receptor pyrin domain-containing protein 3 (NLRP3) inflammasome signaling pathways mediate the pathogenesis of intestinal inflammation. , Thus, the macrophage polarization modulation and inflammatory cytokine production by modulating various inflammatory signaling pathways can be a potential therapeutic approach for colitis.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In particular, the regulation of macrophage polarization through the transplantation of gut microbiota is a promising effective target for colitis. 9,10 In addition, intestinal inflammation during the development of colitis is characterized by enhanced pro-inflammatory cytokines levels. 11 Furthermore, the toll-like receptor 4 (TLR4)/nuclear factor-kappa B (NF-κB) and NOD-like receptor pyrin domain-containing protein 3 (NLRP3) inflammasome signaling pathways mediate the pathogenesis of intestinal inflammation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Together these observations suggest that background diet composition can abrogate the protective properties of FOS. Wang et al 51 investigated the effectiveness of a 4‐week multifibre mix diet, including 49% FOS, in IL‐10−/− mice with spontaneous colitis. A significant decrease in colitis was observed which was associated with reduction of Th1/Th17 cells in lamina propria, reduced inflammatory cytokines and chemokines, and a decrease in members of Proteobacteria in faecal samples.…”
Section: Prebiotics and Fibrementioning
confidence: 99%